Teachers at risk: Depressive symptoms, emotional intelligence, and burnout during COVID-19 - Sánchez-Pujalte, Laura; Gómez Yepes, Talía; Etchezahar, Edgardo; Navarro Mateu, Diego (Frontiers in Public Health, 2023)
Background Previous studies indicated that depressive symptoms are common among teachers due to job stress and difficulty in managing emotions. The aim of this research was to determine the levels of depressive symptomatology in a sample of secondary school teachers who worked during the COVID-19 pandemic and to analyze the relationships with their levels of burnout and emotional intelligence. Methods The study involved 430 secondary school teachers residing in Madrid (Spain) who worked during the COVID-19 pandemic. Participants' age was between 25 and 60 (M = 41.40; SD = 11.07) and the gender distribution was 53.72% men and 46.28% women. We used the Spanish version of the Patient Health Questionnaire (PHQ-9), the Maslach Burnout Inventory Educators Survey (MBI-ES) and the Trait Meta-Mood Scale (TMMS-24). Results The main results indicated that teachers presented high means of depressive symptomatology, with women obtaining higher scores than men. Significant relationships were also observed between the levels of depressive symptomatology and the dimensions of burnout and emotional intelligence. Finally, the three dimensions of emotional intelligence would contribute to the depressive symptomatology of teachers, while of the burnout dimensions only Emotional Exhaustion would make a contribution. Conclusion The possible consequences of depressive symptomatology in teachers during the pandemic are discussed, as well as the need to enhance protective factors such as emotional intelligence and to study burnout levels.